A Genealogy of ‘Ilal Al-Hadîth Study (Tracing the Historical Root Gene of Existence and Development The Study of ‘Ilal Al-Hadith) - Ibnu Hajar Ansori; Rahman Rahman; Zikri Darussamin (Jurnal Ushuluddin, 2020)
As a branch of the Hadith’s discipline, the study of ‘Ilal al-Hadîth must have a historical root gene that cannot separate from the figure’s intellection and ideas. The author will examine the emergence and development of that knowledge through this article, together with the paradigm shift in numbers seen from the practice of ta’lîl. In terms of tracking and analysis, the authors use genealogical theory. The results showed that the science of ‘Ilal al-Hadîth was the formulation of rules extracted from the practice of ta’lîl that existed during the companions of the Prophet. This practice documented in the second and third centuries of Hijriyah, then formulated as a scientific discipline in the fourth century to the new century. From the development of this knowledge, it can be illustrated by a pattern of shifting perspectives towards ‘illah, from defects that are general and evident, to special notes, which are not clear and found in the Hadith that seem authentic